Remarkable catalytic effect of Ni and ZrO2 nanoparticles on the hydrogen sorption properties of MgH2. (22nd January 2022) - Tome, Kudzaishe Caren; Xi, Senliang; Fu, Yuanyi; Lu, Chang; Lu, Ni; Guan, Meili; Zhou, Shixue; Yu, Hao
Abstract: In the present study, the catalytic effect of Ni and ZrO2 nanoparticles on the hydrogen absorption and desorption properties of MgH2 has been investigated. The MgH2 nanocomposites were prepared by high-energy ball-milling. The morphology, phase structure, thermal behavior, and hydrogen storage properties of the materials were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), temperature-programmed desorption (TPD), differential scanning calorimetry (DSC), and the pressure-composition temperature (PCT) methods. ZrO2 and Ni nanoparticles were homogenously dispersed into the MgH2 matrix. The calculated apparent activation energy for dehydrogenation was 63.4 kJ/mol, which was decreased by 80.1 kJ/mol compared to that of as-milled MgH2 . As a result, MgH2 +5 wt.%Ni+5 wt.%ZrO2 demonstrated improved dehydrogenation and hydrogenation kinetics at 310 °C. The MgH2 +5 wt.%Ni+5 wt.%ZrO2 sample released about 6.83 wt.% and absorbed about 6.10 wt.% in less than 30 min. Therefore, the co-catalysis of Ni and ZrO2 significantly enhances the hydrogenation and dehydrogenation properties of MgH2 . Graphical abstract: Image 1 Highlights: Ni and ZrO2 are used as catalysts to enhance the storage properties of MgH2 . The co-catalysis leads to crystal defects that result in fast sorption kinetics. The desorption Ea of MgH2 + 5 wt%Ni+5 wt%ZrO2 is reduced to 63.4 kJ/mol.